2007
DOI: 10.1007/bf02848771
|View full text |Cite
|
Sign up to set email alerts
|

Does pravastatin therapy affect cardiac enzyme levels after percutaneous coronary intervention?

Abstract: Serum cardiac enzyme elevation after percutaneous coronary intervention (PCI), a relatively common complication, is a prognostic determinant of long-term outcome in patients who undergo these procedures. Statins are postulated to reduce such complications. This study investigated the short-term effects of pravastatin on serum creatine kinase myocardial isoform (CK-MB) and serum cardiac troponin I (cTpI) levels after elective PCI. Of 93 patients studied, 72 (77.4%) were men, and 21 (22.6%) were women (mean age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 43 publications
1
18
0
10
Order By: Relevance
“…The pre-PCI bolus of unfractionated heparin was similar: 5000 IU in the studies by Yun et al 19 and Jia et al, 26 50 to 80 IU/kg in the study by Veselka et al, 22 70 to 100 IU/kg in the studies by Bozbas et al 24 and Cay et al, 28 100 IU/kg in the study by Hara et al, 27 and 70 IU/kg in the 3 ARMYDA trials, 16,18,20 the 2 studies by Briguori et al, 17,21 and the study by Kinoshita et al 25 In STATIN STEMI (Efficacy of HighDose Atorvastatin Loading Before Primary Percutaneous Coronary Intervention in ST-Elevation Myocardial Infarction), 23 weight-adjusted unfractionated heparin was given to achieve a target activated clotting time of Ͼ300 seconds in the absence of glycoprotein IIb/IIIa inhibitors and 200 to 300 seconds with glycoprotein IIb/IIIa inhibitors. Bivalirudin was used instead of unfractionated heparin in 10% of patients in ARMYDA-RECAPTURE 20 and enoxaparin in 37% of those in the study by Yun et al 19 Patients in all studies were pretreated with aspirin; the ARMYDA trials and STATIN STEMI 16,18,20,23 used 600 mg of clopidogrel as a loading dose, 5 studies 19,21,22,24,28 used a 300-mg loading dose, 3 studies 17,25,26 used either ticlopidine or clopidogrel (75 mg/d) starting Ն3 days before PCI, and ticlopidine or cilostazol was given in the study by Hara et al 27 Glycoprotein IIb/IIIa inhibitors were not used in 4 studies, 22,24,25,27 whereas such agents were administered, at the discretion of the operator, in the following proportions of patients in the other studies: 52% in the studies by Briguori et al, 17 24% in ARMYDA-ACS, 18 20% in ARMYDA 16 and in the study by Jia et al, 26 14% in NAPLES (Novel Approaches for Preventing or Limiting Events) II 21 and in the study by Cay et al, …”
Section: Main Features Of Included Studiesmentioning
confidence: 84%
See 4 more Smart Citations
“…The pre-PCI bolus of unfractionated heparin was similar: 5000 IU in the studies by Yun et al 19 and Jia et al, 26 50 to 80 IU/kg in the study by Veselka et al, 22 70 to 100 IU/kg in the studies by Bozbas et al 24 and Cay et al, 28 100 IU/kg in the study by Hara et al, 27 and 70 IU/kg in the 3 ARMYDA trials, 16,18,20 the 2 studies by Briguori et al, 17,21 and the study by Kinoshita et al 25 In STATIN STEMI (Efficacy of HighDose Atorvastatin Loading Before Primary Percutaneous Coronary Intervention in ST-Elevation Myocardial Infarction), 23 weight-adjusted unfractionated heparin was given to achieve a target activated clotting time of Ͼ300 seconds in the absence of glycoprotein IIb/IIIa inhibitors and 200 to 300 seconds with glycoprotein IIb/IIIa inhibitors. Bivalirudin was used instead of unfractionated heparin in 10% of patients in ARMYDA-RECAPTURE 20 and enoxaparin in 37% of those in the study by Yun et al 19 Patients in all studies were pretreated with aspirin; the ARMYDA trials and STATIN STEMI 16,18,20,23 used 600 mg of clopidogrel as a loading dose, 5 studies 19,21,22,24,28 used a 300-mg loading dose, 3 studies 17,25,26 used either ticlopidine or clopidogrel (75 mg/d) starting Ն3 days before PCI, and ticlopidine or cilostazol was given in the study by Hara et al 27 Glycoprotein IIb/IIIa inhibitors were not used in 4 studies, 22,24,25,27 whereas such agents were administered, at the discretion of the operator, in the following proportions of patients in the other studies: 52% in the studies by Briguori et al, 17 24% in ARMYDA-ACS, 18 20% in ARMYDA 16 and in the study by Jia et al, 26 14% in NAPLES (Novel Approaches for Preventing or Limiting Events) II 21 and in the study by Cay et al, …”
Section: Main Features Of Included Studiesmentioning
confidence: 84%
“…In the last few years, prospective randomized studies have evaluated the issue of whether a statin pretreatment, with fixed doses of a specific agent for a short, definite period, may provide periprocedural cardioprotection in the setting of PCI; the majority of such studies demonstrated a benefit, 16 -21,23,25-28 but they did not include large numbers of patients, and 2 studies were not confirmatory. 22,24 Therefore, only pooled analyses that include a large patient population may help to achieve definitive results; a meta-analysis 34 was initially performed on this issue, but it had relevant limitations because it included only 2 prospective trials, which were added into the same analysis as retrospective studies. Three other meta-analyses [35][36][37] have been published recently that demonstrated the effectiveness of a statin pretreatment in the setting of PCI, but those investigations did not include the newest randomized studies, were conducted at a study level, did not perform time-to-event and subgroup analyses, did not evaluate occurrence of combined and individual MACE, and considered the incidence of periprocedural myocardial infarc- tion only according to the per trial definition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations